2013
DOI: 10.1016/j.mito.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variations in Madras motor neuron disease

Abstract: Although the Madras Motor Neuron Disease (MMND) was found three decades ago, its genetic basis has not been elucidated, so far. The symptom at onset was impaired hearing, upper limb weakness and atrophy. Since some clinical features of MMND overlap with mitochondrial disorders, we analyzed the complete mitochondrial genome of 45 MMND patients and found 396 variations, including 13 disease-associated, 2 mt-tRNA and 33 non-synonymous (16 MT-ND, 10 MT-CO, 3 MT-CYB and 4 MT-ATPase). A rare variant (m.8302A>G) in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…We did not find any changes in our patient’s exome. Mitochondrial DNA variations may have an indirect role in the pathogenesis of MMND ( Govindaraj et al, 2013 ), but we did not check mitochondrial DNA in this case. Additionally, Valmikinathan et al (1973) suggested that the pathophysiology of MMND might be associated with altered citrate metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…We did not find any changes in our patient’s exome. Mitochondrial DNA variations may have an indirect role in the pathogenesis of MMND ( Govindaraj et al, 2013 ), but we did not check mitochondrial DNA in this case. Additionally, Valmikinathan et al (1973) suggested that the pathophysiology of MMND might be associated with altered citrate metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…[17,18] Further genetic studies need to be undertaken to address the issue of preferential involvement of South Indians. In conclusion, chin fasciculations is a new addition to the clinical profile of MMND.…”
Section: Discussionmentioning
confidence: 99%
“…La forme dite de Madras de maladie motoneuronale, liée à une mutation A8302G dans l'ARNt mitochondrial se traduit par un tableau combinant surdité neurosensorielle, diplégie faciale, dysphagie, dysarthrie, enrouement, amyotrophie linguale, fasciculations [4]. Elle peut également comprendre une atteinte motrice prédominant aux membres supérieurs, des signes pyramidaux, une atrophie optique.…”
Section: Raisonner à Partie De L'atrophie Lingualeunclassified